Design and take up of Austria's Coronavirus short time work model - Dennis Tamesberger; Simon Theurl (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2021)
Short-time work was frequently used in the EU during the COVID-19 pandemic to minimize crisis-related layoffs. This paper focuses on the short-time work (STW) scheme in Austria by exploring the characteristic features of the Austrian Coronavirus STW model and examining how it was utilized. We first give a historical overview of how STW developed in Austria before focusing specifically on the country's STW scheme - one of the most generous among the EU27 - during the course of the coronavirus pandemic. By analyzing relevant data, we identified three key periods in which STW was reformed and slightly modified. We also aim to show how STW take-up rates differ according to gender and sector. Moreover, we consider STW payments alongside sectors and are able to identify those sectors that see a greater benefit from STW. We conclude that the pandemic offered learning effects, thus allowing STW to be used more efficiently in the future by employers in times of crisis.
Keywords: 330; COVID-19 crisis; unemployment; short-time work (STW); labor hoarding; ALMPs